Understanding lawyers' ethics in Canada - Woolley, Alice (LexisNexis, 2023)
"Legal ethics experts Alice Woolley and Amy Salyzyn have written a thorough and scholarly review of the legal and ethical duties every lawyer should follow to manage risk and make prudent decisions in everyday practice. This useful text sets out numerous ethical issues lawyers face in their dealings with clients – complete with analysis, commentary and insight. This book is highly recommended for every lawyer who wishes to represent his or her client to the fullest, while at the same time, remain within the boundaries of legality and of ethical practice. This book is highly recommended for every lawyer who wishes to represent his or her client to the fullest, while at the same time, remain within the boundaries of legality and of ethical practice."-- Provided by publisher.